(9S, 13R)-12-oxo-phytodienoic acid attenuates inflammation by inhibiting mPGES-1 and modulating macrophage polarization via NF-κB and Nrf2/HO-1 pathways. (August 2022) - Zhang, Yan-Yu; Yao, Yun-Da; Chen, Fang; Guo, Xin; Kang, Jun-Li; Huang, Yu-Feng; He, Fan; Dong, Yan; Xie, Ying; Wu, Peng; Zhou, Hua
Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) relieve inflammation by suppressing prostaglandin E2 /cyclooxygenase 2 (PGE2 /COX-2) with cardiovascular and gastrointestinal bleeding risk. Theoretically, suppressing PGE2 through inhibiting the terminal synthase microsomal prostaglandin E2 synthase-1 (mPGES-1) instead of upstream COX-2 is ideal for inflammation. Here, (9 S, 13 R )−12-oxo-phytodienoic acid (AA-24) extracted from Artemisia anomala was first screened as an anti-inflammatory candidate and decreased inducible nitric oxide synthase (iNOS), nitric oxide (NO), mPGES-1, and PGE2 without affecting COX-1/2, thromboxane A2 (TXA2 ) and prostaglandin I2 (PGI2 ). Besides, AA-24 suppressed the differentiation of M0 macrophages to M1 phenotype but enhanced it to M2 phenotype, blocked the activation of NF-κB pathway, and increased the activation of Nrf2 and heme oxygenase-1 (HO-1). Moreover, AA-24 selectively inhibited mPGES-1 and reduced inflamed paw edema in carrageenan-induced mice. In conclusion, AA-24 attenuates inflammation by inhibiting mPGES-1 and modulating macrophage polarization via the NF-κB and Nrf2/HO-1 pathways and could be a promising candidate for developing anti-inflammatory drugs. Graphical Abstract: ga1 Highlights: (9S, 13R)−12-oxo-phytodienoic acid (AA-24) was first extracted from Artemisia anomala . AA-24 selectively reduced inducible PGE2 via inhibiting mPGES-1 but not COX-1/2 in vivo and in vitro. AA-24 suppressed the differentiation of M0 macrophages to M1 phenotype but enhanced it to M2. AA-24 regulated the activation of NF-κB and Nrf2/HO-1 pathways but not the MAPK pathway. AA-24 could be developed as a promising drug to relieve inflammation.